Welfare implications of competition in a vertical market structure: a case of accumulator industry - Yıldız, Sümeyya. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
The accumulator industry exhibits a typical example of a vertical market structure, where waste accumulators are collected, then recycled in order to extract lead, which is subsequently used as the main input in the production of new accumulators. Through a theoretical model the thesis analyzes the welfare implications of the extent of competition in such a market structure. It replicates the well-known result that there is an incentive for firms to vertically integrate; yet also shows that enforcing competition is not welfare-enhancing.
Keywords: Marketing -- Management.; Industrial organization (Economic theory); Competition.